Mechanisms and Intervention Pathways of School-Based Music Therapy for Alleviating Students' Academic Anxiety - Anhui Li (Lecture Notes in Education Psychology and Public Media, 2026)
Against the backdrop of intensifying academic competition and rising learning pressure, academic anxiety has become highly prevalent among student populations. Conventional school-based psychological interventions are constrained by insufficient professional resources and high levels of student resistance. As a flexible, accessible, and non-pharmacological intervention, music therapy has been increasingly integrated into school mental health services. Employing a combination of literature review, case analysis, and comparative research, this study examines three core functioning mechanisms of music therapy—emotional regulation, cognitive defusion, and interpersonal support. It further proposes a three-tiered intervention model and analyzes key influencing factors from both intervention design and individual student perspectives. Evidence from studies on Orff-based group music therapy indicates that group music interventions can significantly alleviate anxiety symptoms, and artificial intelligence technologies can facilitate its scalable implementation in school settings. Currently, the field faces two prominent bottlenecks: a shortage of trained professionals and insufficient targeted empirical evidence. Future efforts should strengthen workforce development, promote interdisciplinary collaboration, and establish standardized school-based intervention systems. This study provides practical guidance for optimizing the mechanism of music therapy in alleviating academic anxiety within school mental health intervention frameworks.